Early short-term treatment with neutralizing human monoclonal antibodies halts SHIV infection in infant macaques - Hessell, Ann J. (2016)
Prevention of mother-to-child transmission (MTCT) of HIV remains a major objective where antenatal care is not readily accessible. We tested HIV-1–specific human neutralizing monoclonal antibodies (NmAbs) as a post-exposure therapy in an infant macaque model for intrapartum MTCT. One-month-old rhesus macaques were inoculated orally with the simian-human immunodeficiency virus SHIVSF162P3. On days 1, 4, 7 and 10 after virus exposure, we injected animals subcutaneously with NmAbs and quantified systemic distribution of NmAbs in multiple tissues within 24 h after antibody administration. Replicating virus was found in multiple tissues by day 1 in animals that were not treated. All NmAb-treated macaques were free of virus in blood and tissues at 6 months after exposure. We detected no anti-SHIV T cell responses in blood or tissues at necropsy, and no virus emerged after CD8+ T cell depletion. These results suggest that early passive immunotherapy can eliminate early viral foci and thereby prevent the establishment of viral reservoirs.